1955
DOI: 10.1111/j.1467-6494.1955.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Task Attitudes in Word Association, Projective and Nonprojective1

Abstract: V-iONSTRUCTivE theorizing and research on the projective process have been greatly hampered by the general tendency to accept and preserve as "given" the particular set of conditions which happened to be specified originally for each of the various projective tests We now have a wide variety of "standard" projective conditions varying all of the way from the unstructured blots and free directions of the Rorschach test to the highly structured stimulus words and rigid directions of the word-association test Hen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
1

Year Published

1958
1958
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 3 publications
3
16
1
Order By: Relevance
“…The results were analyzed m terms of the reaction time and content of the associative responses The statistical treatment is restricted to an analysis of the results for the 15 adjective stimulus words, since adjective stimuli have been found to be well suited to yield differentiation between stimulus-bound and subject-bound associates (7) Table 1 presents a comparison of the spontaneous tempo of associative reaction (based upon individual medians) adopted by 5"s low or high on scales R, T, and S i's with low scores on any of the three scales were relatively prompt m their reactions, whereas i's high on these scales delayed their reactions However, only m the case of scale R is there a statistically reliable difference {p = 025) between the low and high groups Thus the results clearly confirm our prediction that individuals who are typically impulsive choose to react more promptly than do inhibited individuals on an association test administered under free conditions The results for scale T fail to confirm our prediction…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations
“…The results were analyzed m terms of the reaction time and content of the associative responses The statistical treatment is restricted to an analysis of the results for the 15 adjective stimulus words, since adjective stimuli have been found to be well suited to yield differentiation between stimulus-bound and subject-bound associates (7) Table 1 presents a comparison of the spontaneous tempo of associative reaction (based upon individual medians) adopted by 5"s low or high on scales R, T, and S i's with low scores on any of the three scales were relatively prompt m their reactions, whereas i's high on these scales delayed their reactions However, only m the case of scale R is there a statistically reliable difference {p = 025) between the low and high groups Thus the results clearly confirm our prediction that individuals who are typically impulsive choose to react more promptly than do inhibited individuals on an association test administered under free conditions The results for scale T fail to confirm our prediction…”
Section: Resultscontrasting
confidence: 69%
“…The fact that the results generally fail to support our prediction of a relation between extroversion-introversion of the thinking type and the two patterns of association may be an artifact produced by the close relation of Guilford's scale T to maladjustment Since it has already been shown that maladjustment scores are reliably related to the two associative patterns (7), it seems plausible to assume that the maladjustment variable worked in opposition to the extroversion-introversion variable in the present study According to Guilford, both our Low T and High T groups were maladjusted, so that their associative patterns would tend to be similar because of this factor in common value systems wjis introduced here to include another aspect of the obective-subjective dimension of personahty which might be more closely related to our two patterns of association (and less directly related to maladjustment) than Guilford's measures of extijoversionmtroversion Knowledge of an individual's dominant value system should provide very definite information about the specific standard of evaluation that he will apply in situations providing freedom of choice One should be able to predict from his values the general manner in which a person will interpret the task of word association, the kind of evaluative choices he will make between alternative responses, and the kind of responses that he will find personally most meaningful Moreover, on the basis of a theoretical analysis of the relation of the six value systems to our problem, we came to the conclusion that these values could be classified under the following two relevant categories…”
Section: Dtscusstonmentioning
confidence: 99%
See 2 more Smart Citations
“…Kieldergaard reported that about as many popular responses are elicited by such antonym-set instructions as were elicited by Jenkins' instructions to give popular responses. Siipola, Walker, and Kolb (1955) reported that, when Ss are asked to give associations under an extreme speed set, they give more antonJ~responses than they do under stand.ard free-association instructions. It appears that antonym responses are ones Ss find obvious.…”
mentioning
confidence: 99%